(untitled) (Brazilian Journal of Behavioral and Cognitive Therapy, 2014)
This paper presents a critical review of diagnostic criteria and determination models of anorexia and bulimia, used in the International Journal of Eating Disorders. It is particularly questioning the notion of internal determination of these disorders, emphasizing this mode of interpretation with an analysis of the weight phobia (fat phobia). The recovery of this biobehavioral model of anorexia induced by physical activity, and the set of experiments that underlie it, aims to bring the consideration of alternative explanations for eating disorders without the need to appeal to emotional or cognitive variables as determinants of these disorders